PENGEMBANGAN EKONOMI DAN IPTEK PADA KUB DELIMA DAN KUB CITRA KUSUMA KABUPATEN JEPARA - Saptariana, Saptariana; Lestari, Hanna; Widjanarko, Dwi (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
IbM’s devotion partner is a joint business group (KUB) Delima and KUB Citra Ku- susma who are entrepreneur in the field of food. The problems that arise are: (1) production aspect, want to increase production quantity but constrained equipments possessed very sim- ple and minimal (2) quality aspect, the product has not got PIRT license and not yet neat, so it needs to be improved for marketing expansion, (3) ) aspects of hiegene and sanitation, not con- sidering individual hygiene and equipment and environmental sanitation (4) aspects of busi- ness  management  and  marketing,  administrative  and  financial records  need  to  be  improved. For extensive marketing requires an attractive packaging and there is a manufacturer address. Based on the problems faced by the science and technology community partners (IbM) above, the solutions offered are: (1) Applied one unit of oven, (2) Applied one large mixer unit to stir the dough, (3). Produced cake recipe terstansdar from the amount of materials, processing techniques, neatness form and uniformity level of maturity. (4) Known the results of organoleptic test: in terms of taste, color, aroma and texture and known test results of the public / consumer against the cake in produc- tion. (5). The resulting design and quality of cake packaging is more interesting, (6). Assisted with the arrangement of PIRT permits for cakes made by KUB Delima and KUB Citra Kusuma, (7). Known nutritional content of cakes in the form of content: carbohydrates, fats, proteins, water content and ash content. (8). On business management (bookkeeping and administration) recorded complete and neat. (9). On marketing already using brochures and packaging already address the manufacturer. (10). The increased partner profits which in turn can increase the income and welfare of KUB members. (11). Generated scientific articles in national journals in order to publish the results of the activities